Fraud and Abuse of Circumstances as Grounds for the Annulment of Prenuptial Agreements: A Normative Analysis of Defects of Will in Indonesian Civil Law - Cinta Aisyah Putri; Dwi Aryanti Ramadhani (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The natural human capacity for coexistence and procreation is realized through marriage, a legal bond between a man and a woman. Prenuptial agreements, which should serve as legal instruments for justly defining rights and obligations, are often misused for unilateral gain, especially when there are signs of deception or abuse of circumstances that harm one spouse. This normative juridical study aims to examine the legal standing and consequences of prenuptial agreements that mislead one of the partners, utilizing statutory and case approaches. The findings indicate that agreements containing elements of deception, either through fraud (violating subjective requirements), or those contradicting statutory law (violating objective requirements), may be annulled or declared void by law. The legal consequences include the annulment of the agreement, which reverts the asset status back to marital community property, and the potential for civil claims for compensation based on Tort (Article 1365 Civil Code) to recover losses and ensure the principle of good faith.